Timber sales-- Quinaielt Indian Reservation : hearings before the Subcommittee on Indian Affairs of the Committee on Interior and Insular Affairs, United States Senate, Eighty-fifth Congress, first session, April 12, 15, May 29, and June 3, 1957 (United States Government Printing Office, 1957)
Considers Bureau of Indian Affairs administration of the Quinaielt Indians timber sales program.